The Effects of Health Education to The Knowledge Level and Attitude of Adolescents’ Reproductive Health - Saurmian Sinaga; Lidya Natalia (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Reproductive health is a healthy state physically, mentally, and socially intact, not solely free from diseases or disabilities related to reproductive systems, functions, and processes. Health education is the process of improving people's ability to maintain and improve their health. The purpose of this study was to determine the effect of health education on the level of knowledge and attitudes of adolescents about reproductive health in class VIII Madrasah Tsanawiyah Baabussalaam Bandung. The design of this research was the Pre-Experimental Designs with One-Group Pretest-Posttest Design, the sampling technique used the total sampling with 91 respondents. The result of the research showed that before health education, a small part of all respondents (37,4%) have enough knowledge after given health education most of all respondents (73%) have good knowledge about reproductive health. Prior to being given health education some of the respondents (57.1%) had negative attitudes, after being given health education most of all respondents (65.9%) had a positive attitude about reproductive health. The result of the Wilcoxon test analysis for the knowledge and attitude variables were significant (P-Value 0.000 ≤ 0,05). It can be concluded that there is an influence of health education to the level of knowledge and attitude of adolescent about reproduction health in class VIII Madrasah Tsanawiyah Baabussalaam city of Bandung. Nurses are expected to maximize their role as an educator in providing health education for adolescents, especially on adolescent reproductive health. Keywords: Knowledge, Attitude, Reproductive Health